Raman Spectroscopy Investigation of the Polar Vibrational Modes in CuB2O4. (January 2016) - Tomov, V; Rafailov, P M; Yankova, L
Abstract: We report results of polarized Raman spectroscopy of piezoelectric copper metaborate CuB2O4 (space group I ¯42d, Z = 12) in the range from 80 to 1300 cm-1. Due to the dense population of the phonon spectra we carried out angular-dependent measurements by rotating the sample in different crystallographic planes thus performing gradual transitions from one polarization configuration to another. The different angular dependence of the scattering intensities of vibrational modes of different symmetries allowed us to obtain Raman signal from some transversal optical (TO) modes of E-symmetry and to demonstrate the singlemode behavior of the B2 modes by means of transition from TO character to longitudinal optical (LO) character of these phonons.